Daylight photodynamic therapy for prevention of new actinic keratosis and keratinocyte carcinomas in organ transplants. A cryotherapy‐controlled randomized clinical trial. (5th February 2020) - Bernad, I.; Aguado, L.; Núñez‐Córdoba, J.M.; Redondo, P.
Abstract: Background: Organ transplant recipients (OTR) have a higher risk of actinic keratosis (AK) and keratinocyte carcinomas (KC). There are no clinical trials assessing the effectiveness of daylight photodynamic therapy (DPDT) to prevent new AK and KC in OTR. Objectives: To determine whether repeated treatments of field cancerization with DPDT are effective in preventing new AK and KC in OTR. Methods: A randomized, intra‐subject controlled, evaluator‐blind, split‐face and/or scalp trial, from April 2016 to October 2018. Participants were OTR older than 18 years, 1‐year posttransplant, with at least 5 AK on each hemi‐face/hemi‐scalp. One side received six field treatments with DPDT: two sessions 15 days apart at baseline, two at 3 months and two at 9 months after baseline. Control side received lesion‐directed treatment with cryotherapy (double freeze–thaw) at baseline, 3 and 9 months. Total number of lesions (AK and KC) at 21 months, number of new AK and KC at 3, 9, 15 and 21 months and treatment preferences were analysed. Results: Of 24 men included, 23 were analysed at 3 months; and 21, at 9, 15 and 21 months. Mean (SD) age was 69.8 years (9.2). The total number of lesions at 21 months was 4.7 (4.3) for DPDT and 5.8 (5.0) for control side; P = 0.09. DPDT showed significantly lower means [SD] of new lesions compared to control side at 3 months (4.2 [3.4] vs. 6.8 [4.8]; P < 0.001), 9 months (3.0 [3.3] vs. 4.3 [3.4]; P = 0.04) and 15 months (3.0 [4.6] vs. 4.8 [5.0]; P = 0.02), and non‐significant at 21 months (3.7 [3.5] vs. 5.0 [4.5]; P = 0.06). Most participants preferred DPDT. Conclusion: DPDT showed potential effectiveness in preventing new AK and KC in OTR by consecutive treatments of field cancerization. The preference for DPDT could facilitate adherence to the long‐term treatment necessary in these patients.